2004
DOI: 10.1212/01.wnl.0000120550.00643.dc
|View full text |Cite
|
Sign up to set email alerts
|

Glial and neuronal proteins in serum predict outcome after severe traumatic brain injury

Abstract: These results suggest that determination of serum levels of glial and neuronal proteins may add to the clinical assessment of the primary damage and prediction of outcome after severe traumatic brain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
244
2
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 362 publications
(266 citation statements)
references
References 49 publications
11
244
2
5
Order By: Relevance
“…For example, GFAP serum concentrations Ͼ1.5 ng/mL were found to be predictive of death (85% sensitivity; 52% specificity) or poor outcome (GOS at 6 months; 80% sensitivity; 59% specificity). 15 Consistent with its brain-specific expression, GFAP levels were found to be normal in multitrauma patients that did not have brain injury. 24 …”
Section: Glial Fibrillary Acidic Proteinmentioning
confidence: 68%
See 3 more Smart Citations
“…For example, GFAP serum concentrations Ͼ1.5 ng/mL were found to be predictive of death (85% sensitivity; 52% specificity) or poor outcome (GOS at 6 months; 80% sensitivity; 59% specificity). 15 Consistent with its brain-specific expression, GFAP levels were found to be normal in multitrauma patients that did not have brain injury. 24 …”
Section: Glial Fibrillary Acidic Proteinmentioning
confidence: 68%
“…Increased levels of this protein have been proposed as biomarkers of poor outcome. For example, Vos et al 15 demonstrated that in patients with severe TBI, serum S100B concentrations Ͼ1.13 ng/mL were associated with increased mortality (100% sensitivity; 41% specificity) and morbidity (88% sensitivity; 43% specificity). The low basal levels of S100B in human serum allow increases in the concentrations of this protein to be very sensitive indicators of brain injury.…”
Section: S100bmentioning
confidence: 99%
See 2 more Smart Citations
“…(16) In severe TBI, S100B correlates with a short time outcome (death or survival), functional prognosis in 6 months and with severity criteria of TBI such as the Marshall score and the ISS. (15,23,24) Serum levels of S100B, assessed in the first hours after severe TBI have been better predictors of long term prognosis, when assessed by the GOS scale than the GCS and the CT Marshall scale. (25) Because S100B has a halflife of about 2 hours, increased values due to primary brain damage should return to baseline levels in 12 to 24 hours.…”
Section: S100bmentioning
confidence: 99%